Kualitas Fisik Biskuit Pakan yang Berbeda Bahan Penyusunya - Joko Daryatmo; Sugiyanti Sugiyanti (Universitas Muhammadiyah Purworejo, 2021)
This study aims to determine the physical quality (water content, water absorption, and density) of corn leaf biscuits and corn husk biscuits compared with field grass biscuits conducted in the Animal Feed laboratory and the Feed Quality Testing Laboratory of the Polytechnic of Agriculture Development Yogyakarta-Magelang. The study was conducted using a Completely Randomized Design (CRD) with 3 treatments and 6 replications, namely biscuits from field grass and 15% molasses as a control (P0), corn leaf biscuits and 15% molasses (P1) and biscuits from corn husk and molases 15% (P2). The results of P0, P1 and P2 were equally good, in the physical quality test of the absorption capacity and density of feed biscuits. The lowest water content (P<0.05) was found in corn husk biscuits (P2). It was concluded that the biscuits, corn leaves and corn husk produced the same physical quality of water absorption and feed biscuits density, except for the water content, namely corn husk biscuits (P2) had the lowest water content values ​​compared to corn leaf biscuits and field grass biscuits.